(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
This paper uses a model reference adaptive system (MRAS) to build an improved sensorless rotor-field oriented control (RFOC) induction motor (IM) drive in all speed ranges. However, in the presence of external disturbances and parameter variations, the linear tuning method of the Proportional Integrator (PI) controller in the MRAS adaptation mechanism degrades motor performance. An advanced MRAS-based synergetic technique is proposed to develop two suitable adaptation mechanisms that generate slip speed and stator resistance estimates. The reference and adjustable models are developed in the synchronous rotation coordinate system (d-q frame). The effectiveness of the proposed control algorithm was evaluated under various operating conditions using a specific sensorless IM benchmark and the MATLAB/Simulink software environment.